Correlation between Kir4.1 expression and barium-sensitive currents in rat and human glioma cell lines. (10th January 2021) - Madadi, Annett; Wolfart, Jakob; Lange, Falko; Brehme, Hannes; Linnebacher, Michael; Bräuer, Anja U.; Büttner, Andreas; Freiman, Thomas; Henker, Christian; Einsle, Anne; Rackow, Simone; Köhling, Rüdiger; et al.
Highlights: Differential expression of Kir4.1 in human patient derived glioma cell lines. Reduction of Kir4.1 in human gliomas compared to healthy human brain tissue. Shift to more depolarized resting membrane potentials in glioma cells. Differences in Ba 2+ -sensitive current voltage relationship in glioma cells. Abstract: Gliomas are the most common primary brain tumors and often become apparent through symptomatic epileptic seizures. Glial cells express the inwardly rectifying K + channel Kir4.1 playing a major role in K + buffering, and are presumably involved in facilitating epileptic hyperexcitability. We therefore aimed to investigate the molecular and functional expression of Kir4.1 channels in cultured rat and human glioma cells. Quantitative PCR showed reduced expression of Kir4.1 in rat C6 and F98 cells as compared to control. In human U-87MG cells and in patient-derived low-passage glioblastoma cultures, Kir4.1 expression was also reduced as compared to autopsy controls. Testing Kir4.1 function using whole-cell patch-clamp experiments on rat C6 and two human low-passage glioblastoma cell lines (HROG38 and HROG05), we found a significantly depolarized resting membrane potential (RMP) in HROG05 (-29 ± 2 mV, n = 11) compared to C6 (-71 ± 1 mV, n = 12, P < 0.05) and HROG38 (-60 ± 2 mV, n = 12, P < 0.05). Sustained K + inward or outward currents were sensitive to Ba 2+ added to the bath solution in HROG38 and C6 cells, but not in HROG05 cells, consistent with RMP depolarization. While immunocytochemistry confirmed Kir4.1 in all three cell lines including HROG05, we found that aquaporin-4 and Kir5.1 were also significantly reduced suggesting that the Ba 2+ -sensitive K + current is generally impaired in glioma tissue. In summary, we demonstrated that glioma cells differentially express functional inwardly rectifying K + channels suggesting that impaired K + buffering in cells lacking functional Ba 2+ -sensitive K + currents may be a risk factor for increased excitability and thereby contribute to the differential epileptogenicity of gliomas.